Disaster Preparedness Snakes and Ladders: Educational Games Training Volcano Mitigation - Tyas, Rizki Arumning; Humaidi, Afnan; Kurniasih, Latifah; Darmaningwan, Muhammad Guntur Persada (Journal of Multidisciplinary Science, 2025)
The lack of understanding about volcano disaster mitigation has an impact on the large number of victims of eruption disasters, especially among children. The use of appropriate learning media will facilitate the delivery of information and children's understanding of mitigation materials. This study aims to produce snakes and ladders games as a learning medium on volcano disaster mitigation materials, knowing the feasibility of learning media for snakes and ladders disaster preparedness. This type of research is research and development. Media testing is done by providing material validation and media validation to experts and questionnaires to students to determine the feasibility of snakes and ladders learning media. Media testing is carried out by validating learning experts consisting of material experts and media experts as well as questionnaires on students to determine student responses to the learning media developed. The results of media validation by experts show that the learning media developed is very suitable for the material and is very feasible to be used as a learning medium. The response of students is very interested in learning media in the form of educational games snake and ladder disaster preparedness.